Metode William Fleksi pada Low Back Pain: Studi Literatur - Ika Rahmawati; Devi Nurmalia; Sarah Ulliya; Bambang Edi Warsito (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2022)
Background: Low back pain (LBP) is a clinical syndrome in which the main symptom is painful or uncomfortable feeling in lower back area. Work factor is one of many factors that can caused LBP, which may be triggered by carelessness and unergonomic work posture. There is a physical therapy that can be applied to reduce the pain of LBP sufferer namely William’s Flexion Exercise.Objective: To know the effect of William’s Flexion Exercise in reducing the pain of LBP sufferer.Method: This research was a literature review. Literatures were gathered from Google Scholar and PubMed database with low back pain and William’s flexion exercise as the keyword. Data was analysed using PRISMA flow diagram with inclusion criteria such as full text format, published between 2015-2020; written in Bahasa Indonesia and nationally published; written in English and internationally published in Scopus Q1-Q3 indexed journal. While exclusion criteria were literatures which published before 2015 and with double publication.Result: There were seven literatures identified according to the criteria above. From these literatures, it was found that William’s Flexion Exercise was proven in reducing scale of pain of low back pain sufferers and improving joint motion. There were several methods of William’s Flexion Exercise such as pelvic tilting, single knee to chest, double knee to chest, partial sit up, hamstring stretches, bicycling, banding from a chair and squat factor.Conclusion: William’s Flexion Exercise can be an alternative physical therapy to reduce the scale of pain of LBP sufferer. ABSTRAKLatar belakang: Low back pain (LBP) adalah sindrom klinis dengan gejala utama nyeri atau ketidaknyamanan di daerah punggung bawah. Banyak faktor yang dapat menyebabkan LBP, salah satunya adalah faktor pekerjaan. Keluhan nyeri punggung bawah dapat timbul karena kurang berhati-hati dan sikap yang tidak ergonomis selama beraktivitas dalam bekerja. Salah satu terapi fisik yang dapat digunakan untuk mengurangi nyeri pada penderita LBP adalah dengan latihan William Fleksi.Tujuan: Mengetahui pengaruh terapi latihan William Fleksi untuk mengurangi nyeri pada penderita LBP. Metode: Penelitian ini merupakan studi literatur. Literatur dikumpulkan dari database Google Scholar dan PubMed dengan nyeri punggung bawah dan latihan fleksi William sebagai kata kuncinya. Data dianalisis menggunakan diagram alir PRISMA dengan kriteria inklusi seperti format teks lengkap, diterbitkan antara tahun 2015-2020; ditulis dalam Bahasa Indonesia dan diterbitkan secara nasional; ditulis dalam bahasa Inggris dan diterbitkan secara internasional dalam jurnal terindeks Scopus Q1-Q3. Sementara kriteria eksklusi adalah literatur yang diterbitkan sebelum tahun 2015 dan dengan publikasi ganda. Hasil: Ada tujuh literatur yang diidentifikasi sesuai dengan kriteria di atas. Dari literatur-literatur tersebut ditemukan bahwa William's Flexion Exercise terbukti dapat menurunkan skala nyeri pada penderita low back pain dan meningkatkan gerakan sendi. Terdapat beberapa metode William Fleksi, antara lain pelvic telting, single knee to chest, double knee to chest, partial sit up, hamstring stretches, bicycling, banding from a chair dan squat factor.Simpulan: Latihan William Fleksi dapat menjadi alternatif terapi fisik untuk mengurangi skala nyeri pada penderita LBP.